Point of Sales Analysis Gudang Garam Strategic Partnership Program and Sampoerna Retail Community - Adi Putranto, Hanafi; Agustin Rahayu, Hastanti (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Objective – The purpose of this study is to examine how Point of Sales can support the marketing strategy of the Gudang Garam Strategic Partnership Program and Sampoerna Retail Community in Gresik Regency and its impact on sales. Design/methodology/approach – The method used is a descriptive qualitative method followed by observation and in-depth interviews as a representation of the qualitative approach. The informants are store managers totaling 36 stores. Findings – The results obtained by the study indicate that the implementation of Point of Sales in retail stores selling Gudang Garam and Sampoerna cigarettes has been proven to increase operational efficiency. Sales data obtained from Point of Sales shows a positive trend in sales of Gudang Garam and Sampoerna cigarettes. Decisions based on valid data tend to be more effective in achieving marketing goals and increasing sales. Point Of Sales data analysis also reveals consumer behavior patterns such as purchase frequency, most popular products, and purchase time. Research limitations/implications – This research was only conducted in Gresik with two cigarette companies as the object and each has a product item. As a recommendation, the author suggests further research in a different context of cigarette companies. The researcher also suggests that further research with research and development requires a rather long research time Practical implications – This research will encourage companies to pay more attention to Point of Sales in stores with complete sales data, and marketing activities will contribute to increasing sales. Originality/value – The originality lies in determining the model of the interviewees in one district by taking one shop in one sub-district and one cigarette company with a different brand.